The experience of solving the housing problem and housing construction in the daily life of the villagers of Central Kazakhstan in 1964-1985 (Journal of history, 2022)
This article is devoted to the study of the experience of solving housing problems and housing construction, the state of housing of the villagers of Central Kazakhstan in 1964-1985. Based on archival materials from the archives of Kazakhstan and the Russian Federation, the authors analyzed the state of the housing stock and housing construction, considered the causes of problems that have accumulated in the housing and construction business. The study also used interview materials collected among the rural population of a number of districts. As a result, the features of solving the housing problem in the agrarian regions of the region, the consequences and difficulties in construction and housing provision in rural everyday life in Central Kazakhstan were identified. Despite the gradual positive dynamics, the growth of the welfare of the villagers and the increased attention of local authorities to the construction issue in the 70s and the first half of the 80s of the twentieth century, housing security of the population was at a low level. Among the main factors of insufficient development of housing and construction, the authors identified: poor material and technical base, remoteness and dispersion of rural settlements in the region, low level of transport infrastructure, lack of construction specialists, etc. The solution to the problem was largely provided by the entrepreneurial spirit of local leaders and specialists, as well as local residents themselves. The materials of the article can serve as a basis for considering the fundamentals of Soviet state policy in rural areas in the Kazakh SSR during the years of stagnation and problems of social adaptation of rural population in Central Kazakhstan.